John Osborne papers - Osborne, John, 1907-1981.
Correspondence and memoranda; family papers; drafts of published and unpublished articles, reports, columns, and interviews; notes and notebooks; dispatches and news cables; research material; and other papers documenting Osborne's career as a reporter, editor, and columnist for Time, Life, and the New Republic. Much of the collection relates to his New Republic column on national politics and the presidency entitled "The Nixon Watch" that continued as "White House Watch" during the Ford, Carter, and Reagan administrations. Also includes Osborne's World War II reports from Europe and stories on the London blitz, Communist takeover of China, and the Korean War and other articles from his posts in London, Rome, Tokyo, New York, N.Y., and Washington, D.C. Research notes and background material for prospective but unpublished biographies of James Forrestal and John F. Kennedy and a work on the Vietnamese Conflict are also contained in the collection. Correspondents include Henry Robinson Luce.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Library of Congress Prints and Photographs Division.
Author, editor, and journalist. Full name: John Franklin Osborne. Died 1981.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Carter, Jimmy, -- 1924-; Ford, Gerald R., -- 1913-2006.; Forrestal, James, -- 1892-1949.; Kennedy, John F. -- 1917-1963.; Luce, Henry Robinson, -- 1898-1967 -- Correspondence; Nixon, Richard M. -- 1913-1994.; Reagan, Ronald; Life (Chicago, Ill.); New Republic (New York, N.Y.); Time; Foreign correspondents -- England -- London; Foreign correspondents -- Italy -- Rome; Foreign correspondents -- Japan -- Tokyo; Journalism -- New York (State) -- New York; Journalism -- Washington (D.C.); Korean War, 1950-1953 -- Journalism; Presidents -- United States; Vietnam War, 1961-1975.; World War, 1939-1945 -- Journalism -- Europe; London (England) -- History -- Bombardment, 1940-1945.; United States -- Politics and government -- 1969-1974.; United States -- Politics and government -- 1974-1977.; United States -- Politics and government -- 1977-1981.; United States -- Politics and government -- 1981-1989.; Authors; Journalists